The Real-Time Power Monitoring in Building Using IoT Sensing Method and Knowledge Management Approach - Walaiporn Singkhamfu; Kanokwan Chaiyaso; Narisra Laohapatanalert; Nikom Thipnate; Phudinan Singkhamfu (Journal of ICT, Design, Engineering and Technological Science, 2018)
The objective of this research is from overpower consumption problem in the organization by combining the concept of IoT sensing method, which provides online data to a website with the KM-specific technologies. Using knowledge management process is the primary approach to work as the knowledge accumulated, and knowledge distribution method to manipulate power usage procedure in the organization according to data from the monitoring system. Data will collect through in and out the time of staff compared with power using period. The real-time electricity monitoring system determines data as daily, weekly, and monthly. The system installed into two large offices most occupied rooms and also provided statistically calculated to define the hourly energy consumption. The statistical result of the monitoring system is used to one of the factors to create resource planning which is one of knowledge management processes by providing a conceptualized platform for ideas of working without over power consumption limit in the workplace. The result is also valuable to the further analysis of office working hours for each department in the organization. The study shows the efferent data illustration by using the online platform to be one of the driving factors for the working activity development which controlled by knowledge management process to overcome one of the specific problems.